The Notion of the Good from the Perspective of the Roman Law - Chiriluta, Nicusor Tiberiu (Acta Universitatis Danubius. Juridica, 2024)
The present study analyzes the notion of property or owner, according to the vision of the Roman law, which includes the determination of things that can be the objects of property. The power that a man can have over these objects, both in terms of the duration of time and the degree of possession of them and the ways in which ownership can be acquired or lost, is another side of the analysis. The individuals who are able to acquire, transfer or lose their ownership are highlighted separately.